2022
DOI: 10.3390/cancers14123001
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Curcumin and Luteolin Synergistically Inhibit Colon Cancer Associated with Notch1 and TGF-β Signaling Pathways in Cultured Cells and Xenograft Mice

Abstract: This study aimed to select a combination of curcumin and luteolin, two phytochemicals from food, at lower concentrations with a higher inhibitory effect on colon cancer growth and investigate possible molecular mechanisms of this anti-colon cancer effect. By pairwise combination screening, we identified that the combination of curcumin (CUR) at 15 μM and luteolin (LUT) at 30 μM (C15L30) synergistically suppressed the proliferation of human colon cancer CL-188 cells, but the individual chemicals had a little in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The combination C15L30 synergistically suppressed the wound closure (wound healing assay) in CL-188 cells. The combination of Cur and LUT (at 20 mg/kg/day and 10 mg/kg/day, respectively, IP injection, 5 days for 2 weeks) synergistically suppressed tumor growth in CL-188 cell-derived xenograft mice (187). Western blot results showed that protein levels of Notch1 and TGF-β were synergistically reduced by the combination, both in CL-188 cells and xenograft tumors.…”
Section: Colon Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…The combination C15L30 synergistically suppressed the wound closure (wound healing assay) in CL-188 cells. The combination of Cur and LUT (at 20 mg/kg/day and 10 mg/kg/day, respectively, IP injection, 5 days for 2 weeks) synergistically suppressed tumor growth in CL-188 cell-derived xenograft mice (187). Western blot results showed that protein levels of Notch1 and TGF-β were synergistically reduced by the combination, both in CL-188 cells and xenograft tumors.…”
Section: Colon Cancermentioning
confidence: 95%
“…Therefore, combined curcumin and luteolin synergically inhibited colon cancer development by suppressing cell proliferation, necrosis, and migration associated with Notch1 and TGF-β pathways. Colon cancer may be prevented/treated by consuming foods having high levels of luteolin and curcumin in humans (187).…”
Section: Colon Cancermentioning
confidence: 99%
“…Poor solubility of flavonoids has always been a daunting task for scientists, being widely researched to explore their hidden therapeutic mechanisms. As discussed above, luteolin is known to inhibit tumorigenesis in a diverse range of cancers by inhibiting the viability, migration, angiogenesis and invasion [ 11 , 12 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. However, the combination of protein and flavonoids can ameliorate the problems of poor solubility and stability of flavonoids for better utilization.…”
Section: Insight Into the Nanodelivery Of Luteolin In Cancermentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in Figure 1A as currently published: The Figure 1A was accidentally misused from our other similar study. Although the wrong figure cannot affect the conclusion of this paper, we have to use the correct one for this publication.…”
Section: Error In Figurementioning
confidence: 99%